ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA ARITMATIKA SOSIAL MENURUT TEORI KASTOLAN - Safira Seftianingsih Lamalaka; Sukayasa Sukayasa; Dasa Ismaimuza; Welli Meinarni (STKIP Andi Matappa, 2024)
This study aims to analyze student errors and factors causing errors of cognitive style field independent (FI) and field dependent (FD) students. This study used a qualitative method with a descriptive approach to describe the errors of FI and FD students in solving social arithmetic story problems. The research was conducted at SMP Negeri 3 Dampelas with the research subjects amounted to 2 students each representing FI and FD cognitive styles. Data obtained by giving written tests and interviews. FD students and FI students made conceptual, procedural and technical errors. However, FD made more mistakes when compared to FI. This is intended from the errors made by FD students containing all error indicators, while FI students made errors in indicator 1 for conceptual errors, indicator 2 for procedural errors, and indicator 2 in technical errors. The factors causing the occurrence are not understanding the material taught, not being able to solve the problem according to the procedure properly, not being careful in calculations, and not checking back.